Barriers faced by health-care workers in use of personal protective equipment during COVID pandemic at tertiary care hospital Uttarakhand, India: A qualitative study - Maneesh Sharma; Divita Sharma; Ashok Kumar Sharma; Aroop Mohanty; Meenakshi Khapre; C Vasantha Kalyani (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: To reduce the likelihood of transmission of infection to health-care workers (HCWs), personal protective equipment is used. However, wearing personal protective equipment (PPE) increases the risk of heat stress and loss of dexterity, leads to poor compliance to PPE. To address the issues of poor compliance to PPE, it was necessary to gain a deeper understanding about the factors that influence compliance. Thus this qualitative study was planned to explore barriers faced by HCWs while using PPE during a pandemic situation in a tertiary care hospital, Uttarakhand, India. MATERIALS AND METHODS: A exploratory qualitative study was undertaken among health care workers involved in the care of COVID patients. FGDs were done and an unstructured interview guide with open-ended questions was used which helped to explore the factors which can be potential barriers to the HCWs while working wearing PPE. RESULTS: Organizational and individual factors acting as barriers such as unavailability of essential personal protective equipment, a disharmonious work environment, lack of comfort, inadequate size, and quality of PPE were identified as the major barriers in the present study. CONCLUSION: Future efforts to optimize PPE use should focus on to adequate supplies both in quality and quantity can help in avoidance of such barriers. Resources should be prioritized with the needs of the HCWs in the times of pandemic. Regular training and feedbacks are necessary for the satisfaction of HCWs and improving PPE compliance.